IMPLEMENTASI REMUNERASI DOSEN BADAN LAYANAN UMUM PADA UNIVERSITAS BENGKULU - Maesaroh Hasan; Dri Asmawanti (UNIB Press, 2018)
This study aims to describe the implementation of lecturer remuneration system of Public Service Agency at Bengkulu University. Data collection using primary data obtained from interviews to informants, they are the remuneration team University of Bengkulu. Data collection techniques are done by interview and documentation. The analysis used are data collection, data reduction, data presentation and conclusion. The techniques of testing the validity of the data used are the adequacy of the reference, triangulation and reference material. The results of this research showed that remuneration system is new payroll system applied by UNIB precisely in the end of the year 2015. Implementation of performance reporting by lecturer at UNIB conducted every semester and payment is done every three months. The reporting system of lecturer’s remuneration performance at UNIB is still done manually and not integrated with the academic system, so it is not efficient in it’s implementation. In the future, several new remuneration programs have been planned and are being undertaken in the implementation by remuneration teams to support the successful implementation of the BLU remuneration system in UNIB.Key words: Implementation, Public Service Agency